Evaluation of the Antimicrobial Properties of the Essential Oil of Myrtus communis L. against Clinical Strains of Mycobacterium spp. - Zanetti, Stefania; Cannas, Sara; Molicotti, Paola; Bua, Alessandra; Cubeddu, Marina; Porcedda, Silvia; Marongiu, Bruno; Sechi, Leonardo Antonio (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Mycobacterium tuberculosis is the etiological agent of tuberculosis. The World Health Organization has estimated that 8 million of people develop active TB every year and the situation is complicated by an increase of Mycobacterium tuberculosis strains resistant to drugs used in antitubercular therapy: MDR and XDR-TB. Myrtle leaf extracts, used as an antiseptic in Sardinian traditional medicine, have strong antibacterial activity as several investigations showed. In this study we investigated the antimicrobial properties of the essential oil of Myrtus communis against clinical strains of M. tuberculosis and M. paratuberculosis.